Test-based measurement of skill mismatch: a validation of five different measurement approaches using the NEPS - Bischof, Stephan [Verfasser] (My University, 2024)
„Skill mismatch is a key indicator of labour market research that has received significant attention. To date, various approaches of test-based measurement of skill mismatch have been used in research, generating differing results. However, it remains unclear which method is the most valid for measuring skill mismatch. This study provides a comparative validation of five commonly used approaches to test-based measurement of skill mismatches in reading and mathematics to detect the most valid method. Drawing on the 2016 wave of the German National Educational Panel Study (NEPS) Adult Cohort, I find significantly varying distributions for the different measurement approaches, and highly valid skill mismatch measures for the statistical and the mixed approach. Overall, the mixed approach emerges as the most valid method. The findings highlight the critical importance of measurement approaches in skill mismatch research.“ (author’s abstract; BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; 370; Berufliche Qualifikation; Mismatch; Messung; Qualifikationsforschung; Nationales Bildungspanel